Municipal Restructuring in Québec: Some Lessons for Maine - Wihry, David (Maine Policy Review, 2006)
With the push to consolidate municipal and school administrative functions growing stronger in Maine, David Wihry draws upon the recent government consolidation experiences of the Province of Québec to point out some “lessons learned” with applicability to Maine. He notes that any push for substantial municipal restructuring in Maine will depend on the intensity of public concern over issues such as tax burden and economic development, and on the strength of opposing political influences. Wihry suggests that the local impetus to consolidate may never be strong enough without vigorous state leadership and incentives to advance either the discussion of options or the implementation of consolidations in Maine.